Criminal law in the age of the administrative state - Chiao, Vincent (New York, NY : Oxford University Press, 2018)
What is the criminal law for? One influential answer is that the criminal law vindicates pre-political rights and condemns wrongdoing. In Criminal Law in the Age of the Administrative State, Vincent Chiao offers an alternative, public law account. By starting with the political morality of public institutions, rather than the interpersonal morality of private relationships, the public law account makes the case for regarding criminal law and criminal justice as animated by the same political virtues that gave rise to the institutions of the modern administrative and welfare state. Chiao then shows how this approach to criminal justice provides a fresh perspective on a range of problems, from mass incarceration to overcriminalization, to due process and the collateral consequences of a criminal conviction.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 13, 2018).
Keywords: Criminal law -- Philosophy; Criminal justice, Administration of; Public law; Administrative law; Welfare state; Criminal procedure; Law; Laws of specific jurisdictions & specific areas of law